Overview of the use of lifting equipment in auto maintenance in Astana - Nurkusheva С.А.; Bembenek М.; Kostyuchenkova О. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
This article discusses the problem of the effective use of car lifts for passenger cars, as well as the analysis of the technical parameters of lifts at car service stations in Astana. The purpose of the study is to create theoretical foundations for improving the efficiency and safety of the use of lifts at car service enterprises. The object of the study is the labor productivity of a car service with the use of lifting equipment. Based on the analysis of the review of existing structures, a classification has been developed in order to modernize and create new types of lifts, which allows you to evaluate existing lifts. The results of comparing individual types of lifts that are used in the capital of Kazakhstan, criteria for evaluating the effectiveness and their use at a car service station in order to increase the efficiency of their use are presented.